2009
DOI: 10.1016/s1734-1140(09)70085-4
|View full text |Cite
|
Sign up to set email alerts
|

No association of three GRIN2B polymorphisms with lithium response in bipolar patients

Abstract: Abstract:We investigated three polymorphisms in the NMDA receptor 2B subunit gene (GRIN2B) as a candidate gene for lithium response involved in glutamatergic neurotransmission. One hundred five bipolar patients treated with lithium for at least 5 years were analyzed. The lithium response was assessed as excellent -no affective episodes during lithium treatment; partial -50% reduction in the episode index; or no response -less than 50% reduction, no change or worsening in the episode index. Genotypes for the -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 16 publications
0
25
3
2
Order By: Relevance
“…Although no other studies investigating the role of the genes analyzed in the present study have been found, a previous report analyzing several genetic variability at the glucocorticoid receptor gene (NR3C1) showed association between this gene and Li response. 29 The results from the allele and genotype associations comparing the 3 different groups of Li responders (ER, PR, and NR) did not survive multiple testing in our sample. However, when we analyzed these SNPs comparing PR+NR versus ER, we found significant association surviving multiple testing for all of them except the polymorphism in the GRIK2 gene.…”
Section: Discussionmentioning
confidence: 79%
“…Although no other studies investigating the role of the genes analyzed in the present study have been found, a previous report analyzing several genetic variability at the glucocorticoid receptor gene (NR3C1) showed association between this gene and Li response. 29 The results from the allele and genotype associations comparing the 3 different groups of Li responders (ER, PR, and NR) did not survive multiple testing in our sample. However, when we analyzed these SNPs comparing PR+NR versus ER, we found significant association surviving multiple testing for all of them except the polymorphism in the GRIK2 gene.…”
Section: Discussionmentioning
confidence: 79%
“…Encodes inositol polyphosphate-1-phosphatase, one of the enzymes involved in phosphatidylinositol signaling pathways [90] A polymorphism in INPP1 C973A might be associated with the efficacy of lithium [110]. Significant interactions were also found between lithium response and INPP1 SNP rs206472 [14] CREB1 cAMP responsive element binding protein 1…”
Section: Inositol Polyphosphate-1--phosphatasementioning
confidence: 99%
“…The gene was a promising candidate based on its chromosomal location (12p12) and evidence of altered protein expression in bipolar disorder; however, no significant associations were found [32]. In a different study published recently, the same authors found a putative association with two SNPs of the glutamatergic FYN oncogene related to SRC, FGR, YES (FYN) with bipolar disorder in a cohort of 425 bipolar disorder patients and 518 controls [33].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…Szczepankiewicz et al [32] investigated the role of glutamatergic neurotransmission in Li response by investigating SNPs in the N-methyl D-aspartate (NMDA) receptor 2B subunit gene (GRIN2B) in a sample of 105 bipolar disorder patients treated with Li for at least 5 years and assessed for positive response. The gene was a promising candidate based on its chromosomal location (12p12) and evidence of altered protein expression in bipolar disorder; however, no significant associations were found [32].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
See 1 more Smart Citation